Benchmark 2 – Springback of a Jaguar Land Rover Aluminium. Issue 2 (August 2016) - Allen, Martin; Oliveira, Marta; Hazra, Sumit; Adetoro, Oluwamayokun; Das, Abhishek; Cardoso, Rui
Abstract: The aim of this benchmark is the numerical prediction of the springback of an aluminium panel used in the production of a Jaguar car. The numerical simulation of springback has been very important for the reduction of die try outs through the design of the tools with die compensation, thereby allowing for the production of dimensionally accurate complex parts at a reduced cost. The forming stage of this benchmark includes one single forming operation followed by a trimming operation. Cross-sectional profiles should be reported at specific (provided) sections in the part before and after springback. Problem description, tool geometries, material properties, and the required simulation reports are summarized in this benchmark briefing.